Fernando de noronha (State of pernambuco) fishermen’s local ecological knowledge regarding the fish species used as bait - Zeineddine, Gabriela Campos [UNESP]; Barrella, Walter; Rotundo, Matheus; Ramires, Milena (Zeppelini Editorial e Comunicacao, 2022)
Artisanal fishing on Fernando de Noronha is directly related to fishing for bait, since commercial fishing depends on these baits. This work aimed to analyze the local ecological knowledge of fishermen about the biology and ecology of the fish species used as bait on Fernando de Noronha (state of Pernambuco - PE) to support the planning of the local activity. Data collection was carried out through interviews with semi-structured scripts containing questions about the socio-economic profile of the fishermen and the biological and ecological aspects of the species used as bait. The data were analyzed qualitatively and quantitatively, seeking to represent a consensus among the informants and to compare the local ecological knowledge with the scientific literature through the method of comparative cognition and the hypothesis test. Sixty-nine fishermen were interviewed, using false herrings (Harengula clupeola) and mackerel scads (Decapterus macarellus) as their main bait fish, in still fishing and fishing using boats. The hypothesis test, applied to the mentioned results by more than 30% of the fishermen, showed a high degree of agreement between local ecological knowledge and the scientific literature, revealing detailed knowledge of the fishermen on the biological and ecological aspects of false herrings and mackerel scads. Catching bait fish on Fernando de Noronha proved to be extremely important, both for the relationship with artisanal fishing and for the maintenance of local knowledge and culture. The results obtained in this research should foster a very much-needed dialogue between fishermen and those responsible for managing conservation units to create legal and effective mechanisms to meet the demand for bait fish used in commercial fishing and to maintain a sustainable artisanal fishing model for Fernando de Noronha.
O conhecimento ecológico local dos pescadores artesanais de Fernando de Noronha (PE) sobre as espécies de peixes utilizadas como iscas
Keywords: Artisanal fisheries; Conservation units; Ethnoecology; False herrings